1967
DOI: 10.1139/f67-076
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characteristics of Rainbow Trout in the Great Lakes

Abstract: not available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…For summing up tl\e-previous researchers on this subject, the included tables indicating the authors and the affected characters with different environmental factors. Bidgood and Berst (1967) found that rearing temperature and diets for rainbow trout could account for the variations in proportions of body parts. Martin and Sandercock (1Q67) presented a correlation between both counts of pyloric caeca, and number of gill rakers and their development, and the amount of plankton eaten by lake trout.…”
Section: Biometric Studiesmentioning
confidence: 99%
“…For summing up tl\e-previous researchers on this subject, the included tables indicating the authors and the affected characters with different environmental factors. Bidgood and Berst (1967) found that rearing temperature and diets for rainbow trout could account for the variations in proportions of body parts. Martin and Sandercock (1Q67) presented a correlation between both counts of pyloric caeca, and number of gill rakers and their development, and the amount of plankton eaten by lake trout.…”
Section: Biometric Studiesmentioning
confidence: 99%